Empowering Educators: A Study on the Impact of Principals’ Transformational Leadership on Teacher Performance - Radnasari, Devi; Andrianto, Wewen (Al-Qalam Institue, 2025)
This study explores the impact of transformational leadership strategies employed by the principal on improving teacher performance. Transformational leadership, characterized by inspiring and motivating teachers, plays a crucial role in fostering an environment conducive to professional growth. This qualitative case study examines how the principal’s leadership strategies—such as clear vision communication, individualized support, and fostering collaboration—have influenced teacher motivation, engagement, and overall performance. Data were collected through interviews, observations, and documentation, and analyzed using Miles and Huberman’s qualitative data analysis framework. Findings indicate that the principal’s integrated transformational strategies have led to enhanced teacher performance, with teachers reporting greater motivation, adoption of innovative teaching methods, and improved student engagement. The principal’s clear and inspiring vision was also found to play a key role in aligning teachers' individual goals with the broader objectives of the school. This research contributes to the field of educational leadership by providing empirical evidence on the practical application of transformational leadership in a rural school context, highlighting its potential to improve teacher performance even in resource-constrained environments.